Pathogenesis Coronavirus Disease 2019 (COVID-19): Narrative Literature Review - Sofía Lucila Rodríguez Rivera; José Antonio Infante Cantú; Héctor R. Martínez; Enrique Caro Osorio (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
The pathogenesis of COVID-19 occurs in 3 phases according to the pathophysiology and clinical degree. The three phases are grouped into the initial phase of infection, the pulmonary phase, and the hyperinflammatory phase. The initial phase of infection begins with the inoculation of the virus into host cells. This virus infects cells in the airways that line the alveoli. SARS CoV-2 will bind to receptors found on the epithelium of the respiratory tract, gastrointestinal tract, and endothelium of blood vessels and make its way into cells. The second phase is the pulmonary phase. In this phase, there is viral multiplication and inflammation in the lungs. The binding of SARS-CoV-2 to the ACE2 receptor causes ACE2 deficiency and an imbalance of the renin-angiotensin system (RAS). In the third phase, namely hyper inflammation, excessive cytokine production after SARS-CoV-2 infection will increase the permeability of the capillary wall membrane around the infected alveoli, causing edema, pulmonary dyspnea, and hypoxemia. The presence of plasma fluid in the alveoli and loss of elasticity due to decreased surfactant function due to type 2 pneumocyte infection caused by SARS-CoV-2 infection causes acute respiratory distress syndrome in COVID-19 patients.